Deglasiasjon og holocene havnivåendringer i Lofthus, Ullensvang kommune, basert på kvartærgeologisk kartlegging og eksponeringsdatering - Mortensbakke, Kjersti de Lange (The University of Bergen, 2018)
Observations from Quaternary geological mapping, LIDAR-data, aerial photo analysis and results from surface exposure dating via in situ ^10Be are used to reconstruct Holocene sea-level changes and the course of deglaciation in Lofthus, Ullensvang, south-western Norway. Lofthus is a steep-sided valley along Sørfjorden, and approximately 1000 m a.s.l. and to the east lies the Hardangervidda mountain plateau. The history of the deglaciation and the sea-level changes in the late glacial time and holocene along Hardangerfjorden are widely known. However, along Sørfjorden, the longest branch of Hardangerfjorden, valleys have experienced local variations during the same time. For that reason, Lofthus is of interest due to its near location to Hardangerfjorden, the Folgefonna Peninsula and the Hardangervidda mountain plateau where the deglaciation and sea-level history have been investigated. Lofthus is characterized by terrace levels, thick till and colluvium deposits and big boulders. The research aim for this work is to map out and explain landforms and sediments to reconstruct the course of the deglaciation and the processes that have been active after the area became ice-free. A second aim is to reconstruct the sea-level history based on measured terrace levels from this work and discuss the results with sea-level curves and shoreline diagrams from earlier work in the Hardanger area. A well-established hypothesis claims that the Scandinavian Ice Sheet re-advanced during the Younger Dryas and deposited the Herdla-Halsnøy moraines along the coast of western Norway (Mangerud, 1970; Aarseth og Mangerud, 1974). During the maximum position of the ice-front the Hardangerfjorden was filled with ice. A contradictory hypothesis challenges the established hypothesis and proposes ice-free conditions in Hardangerfjorden throughout the Younger Dryas (Helle, 1993; Helle et al., 1997). One argument for an ice-free Hardangerfjorden is that the Osa-Eidfjord moraines in the inner part of Hardangerfjorden are of Younger Dryas age, and ...